(untitled) (Pedagogical Horizons, 2024)
Following a hermeneutic method, this non-empirical paper deals with the question of how and whether habitualised beliefs can change as a result of decades of practical experience as a teacher in the middle-class institution of school. This case study is an example of the effects that these experiences can have on individuals. A certain professional experience is described using the example of a Viennese compulsory school teacher who wrote two books that attracted a great deal of media attention in Austria in the 2010s. Her texts are placed in the context of the organisation of capital structure in Pierre Bourdieu’s writings on school theory.